"You have (rotator cuff related) shoulder pain, and to treat it, I recommend exercise." A scoping review of the possible mechanisms underpinning exercise therapy. (December 2022) - Powell, Jared K.; Schram, Ben; Lewis, Jeremy; Hing, Wayne
Abstract: Background: Exercise is considered to be both essential and at the forefront of the management of rotator cuff-related shoulder pain (RCRSP). Despite this, many fail to substantially improve with exercise-based treatment. Hence, expanding the current knowledge about the possible mechanisms of exercise for RCRSP is critical. Objective: To synthesise the range of mechanisms proposed for exercise in people with RCRSP. Design: Scoping review Methods: A systematic search of the Physiotherapy Evidence Database (PEDro) was conducted from inception to July 3, 2022. Two reviewers conducted the search and screening process and one reviewer extracted the data from each study. Randomised clinical trials using exercise for the management of RCRSP of any duration were included. The PEDro search terms used were "fitness training", "strength training", "stretching, mobilisation, manipulation, massage", "upper arm, shoulder, or shoulder girdle", "pain", and "musculoskeletal". Data were analysed using quantitative and qualitative approaches. Results: 626 studies were identified and 110 were included in the review. Thirty-two unique mechanisms of exercise were suggested by clinical trialists, from which 4 themes emerged: 1) neuromuscular 2) tissue factors 3) neuro-endocrine-immune 4) psychological. Neuromuscular mechanisms were proposed most often (n = 156, 77%). Overall, biomedical mechanisms of exercise were proposed in 95% of cases. Conclusions: The causal explanation for the beneficial effect of exercise for RCRSP in clinical research is dominated by biomedical mechanisms, despite a lack of supporting evidence. Future research should consider testing the mechanisms identified in this review using mediation analysis to progress knowledge on how exercise might work for RCRSP. Highlights: This study explored commonly proposed mechanisms of exercise for RCRSP. Muscle strength and motor control were the most commonly proposed mechanisms. Psychosocial mechanisms were scarcely proposed. Biomedical mechanisms accounted for 95% of proposed mechanisms of exercise. Identified mechanisms of exercise should be tested as possible mediators of recovery.